PESAN DAKWAH DALAM SERIAL FILM “USTAD MILENIAL” (PENDEKATAN ANALISIS SEMIOTIKA ROLAND BARTHES) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This This study examines (1) To find out the meaning of Da'wah in the Flim Series "Ustad Millennials (2) To find out how the meaning of Denotation, Connotation and Myth in Ustad Millenial's film series. The results of this study are the da'wah messages contained in this Ustad Millenial film series are from the four scenes that the researchers chose previously in the form of analysis of da'wah messages using Roland Barthes' theory and da'wah messages in the category of morality, syar'ah da'wah messages and aqidah da'wah messages. The moral message contained in this film is a polite attitude in lecturing. And the syar'ah message contained in this film reaps congregational prayers, reading the Qur'an. While the message of aqidah is early childhood education to form belief in Allah. As Muslims, we are obliged to do all these things.Research implications (1) Film is a form of mass communication behavior and can be used as a medium for delivering messages that will convey da'wah values (2) In watching or watching a series of films, the public must be clever in choosing and receiving messages that is in any film or show that can be seen. (3) For film directors, so that in the future they can create films that are not just entertainment, but presumably they can make films in which there are also da'wah messages that are useful for the audience in everyday life. -day. Especially now that there are many shows or scenes in films that are not worthy of being seen by children. (4) It is hoped that this research will become one of the reference materials in research on Roland Barthes' semiotics about the meaning of da'wah messages contained in a film series.(5 It is hoped that this research can be a reference or consideration for film practitioners in making or producing films that are full of meaning and can provide motivation and enlightenment to the audience.